2012
DOI: 10.1016/j.csda.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Computing and estimating information matrices of weak ARMA models

Abstract: Numerous time series admit weak autoregressive-moving average (ARMA) representations, in which the errors are uncorrelated but not necessarily independent nor martingale differences. The statistical inference of this general class of models requires the estimation of generalized Fisher information matrices. We give analytic expressions and propose consistent estimators of these matrices, at any point of the parameter space. Our results are illustrated by means of Monte Carlo experiments and by analyzing the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The proof is based on a series of lemmas. Similar proofs can be found in the supplementary files of Francq, Roy and Zakoïan (2005) and Boubacar, Carbon and Francq (2011). We begin by proving thatĴ is a consistent estimator of J.…”
Section: B Proof Of Theorem 23mentioning
confidence: 83%
“…The proof is based on a series of lemmas. Similar proofs can be found in the supplementary files of Francq, Roy and Zakoïan (2005) and Boubacar, Carbon and Francq (2011). We begin by proving thatĴ is a consistent estimator of J.…”
Section: B Proof Of Theorem 23mentioning
confidence: 83%
“…There are differences with [Ber74]: (H t (θ 0 )) t∈Z is multivariate, is not directly observed and is replaced by (Ĥ t ) t∈Z . It is shown that this result remains valid for the multivariate linear process (H t (θ 0 )) t∈Z with non-independent innovations (see [BMCF12,BMF11], for references in weak (multivariate) ARMA models). We will extend the results of [BMCF12] to weak FARIMA models.…”
Section: Estimation Of the Asymptotic Matrix I (θ 0 )mentioning
confidence: 85%
“…Following the arguments developed in [BMCF12], the matrix I (θ 0 ) can be estimated using Berk's approach (see [Ber74]). More precisely, by interpreting I (θ 0 )/2π as the spectral density of the stationary process (H t (θ 0 )) t∈Z evaluated at frequency 0, we can use a parametric autoregressive estimate of the spectral density of (H t (θ 0 )) t∈Z in order to estimate the matrix I (θ 0 ).…”
Section: Estimation Of the Asymptotic Matrix I (θ 0 )mentioning
confidence: 99%
“…In the literature, two types of estimators are generally employed: the nonparametric kernel estimator, also called Heteroskedasticity and Autocorrelation Consistent (HAC) estimators (see Andrews (1991) and Newey and West (1987) for general references, and Francq and Zakoïan (2007) for an application to testing strong linearity in weak ARMA models) and spectral density estimators (see e.g. Berk (1974) and den Haan and Levin (1997) for a general references and Boubacar Mainassara et al (2012) for estimating I when θ is not necessarily equal to θ 0 ).…”
Section: Estimating the Asymptotic Covariance Matrixmentioning
confidence: 99%